Inhibition of Effects of Acetylcholine at Neuromuscular Junction by Omeprazole - Abdul Azeem, Aamna Khokhar, Sidra Mumal , Adnan Bashir, Eisha Akram, Sadia Lodhi (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the effect of Omeprazole at neuromuscular junction with and without Pancuronium. Study design: Experimental randomized control study. Place and duration of study: Department of Pharmacology, Islamic International Medical College, Rawalpindi from October 2018 to September 2019 Methods: In this experimental study both a student’s oscillograph and a cumulative dosage response curve were used to record the frog’s rectus abdominis muscle contracting in response to acetylcholine (control group). Three groups’ responses to omeprazole, both before and after adding pancuronium, were noted. The student’s t test was used to conduct statistical analysis of variance (ANOVA) between the groups, and a p-value of 0.05 or below was regarded as statistically significant. Results: By blocking the neurotransmitter acetylcholine, omeprazole in a dose of 3.5 M concentration altered the curve to the right with a mean deviation of 23.7% (SEM ± 20.5). In the presence of 1 g of pancuronium, omeprazole likewise caused a shift of the curve to the right with a mean deviation of 37 percent (SEM ±10.5). The change demonstrated the agonistic impact of omeprazole on NMJ blockers like pancuronium at this concentration and was statistically significant (p < 0.05). Conclusion: Omeprazole in 3.5µM strength inhibits the effects of Acetylcholine at neuromuscular junction, however, it potentiates the effects of neuromuscular blockers like Pancuronium at same strength. Keywords: Acetylcholine, Neuromuscular Junction, Pancuronium, Omeprazole.